Choice of handshape and classifier type in placement verbs in American Sign Language - Frederiksen Anne Therese (Open Linguistics)
This study investigates choice of classifier handshape in the placement verbs MOVE and PUT in American Sign Language (ASL), analyzing data from two deaf ASL signers describing placement events elicited via a semi-structured task. Two questions are addressed in the study: 1) which (handling) handshapes are used with PUT and MOVE for different types of entities, and 2) whether object classifiers can occur with transitive, causative predicates in ASL. The results show that the two signers primarily use three handling handshapes (flat-O, S, and C). Consistent with findings from previous research, these handshapes are generally used to represent entities in an iconic manner based on entity characteristics. Usage of the flat-O handshape extends beyond strictly iconic representation, confirming previous suggestions that it may serve as a generic classifier for handling objects. The study also reports a finding not previously observed for ASL, namely two instances of object classifiers used in transitive predicates, which parallels recent evidence from other sign languages that the relationship between classifier type and argument structure is not categorical. Assimilation and language-specific handshape bias are discussed as factors influencing classifier choice, and the findings are situated within broader principles of body partitioning, perspective, and type of representation in sign languages.